PENGEMBANGAN BAHAN AJAR BERBENTUK E-MODUL BERBANTUAN SIGIL SOFTWARE PADA POKOK BAHASAN MATRIKS UNTUK PESERTA DIDIK KELAS XI - Jannati, Nurul (Jurnal Edukasi dan Penelitian Matematika, 2023)
E-modules are presentations of material in electronic form with links to each lesson, complete with videos, animations and audio presentations for a learning experience. The purpose of this study is to describe teaching materials in the form of e-modules in a valid and practical manner and to describe the effectiveness of teaching materials in the form of e-modules on learning outcomes. This type of research is development research with the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. The data for this research are needs analysis data, validation data, performance data, and effectiveness data. The survey instruments were the Student Characteristics Questionnaire, Self-Assessment Analysis Questionnaire, Youth Module Validation Matrix Questionnaire, One-to-One Evaluation Interview Questionnaire, and Youth Module Matrix Practice Questionnaire. As a result, we find that the material shape of the modular matrix has very good categorical effect sizes (based on validation by two mathematicians). The material format of Young's Matrix coefficients is research based on the resuIts of surveys and interviews and has great practical relevance. The resuIts of the validity evaluation show that the material in the form of a matrix module can improve student learning outcomes.Keywords – e-module, ADDIE Model, Matrix, sigil software